Impact of tenecteplase in intermediate and high risk pulmonary embolism - Thrudeep, S.; Jayakumar, T. G.; Rajesh, G.; Rupesh, G.; Geofi, K.G.; Gagan, S.; Abdulkhadar, S. (International Journal of Advances in Medicine, 2016)
Background: Pulmonary embolism (PE) is a 3rd most common lethal cardiovascular disease. The objective was to study the outcome of high and intermediate risk acute pulmonary embolism (PE) with special reference to Tenecteplase. Methods: Retrospective observational study of clinical features and outcome of high and intermediate risk patients with acute pulmonary embolism treated with Tenecteplase from January 2008 to January 2016. Results: 40 patients who were newly diagnosed to have PE with a mean age of 54 years were included in the study. Dyspnea and syncope were the predominant symptoms in both IR and HR. Most sensitive parameter i.e. D-dimer was positive among all 40 cases but cardiac biomarker troponin was positive in 56.8% cases only. Evidence of RV dysfunction was present all cases with 65% cases had presented with severe pulmonary arterial hypertension. Diagnosis of acute pulmonary embolism was confirmed by MDCT of lung. All confirmed cases of acute PE were administered dose adjusted intravenous tenectaplse. Of the 40 patients, 39 were discharged and were under regular follow up for 6 months. In hospital mortality of HR and IR 11% &3.2% respectively but 2 more cases expired within a span of 7 days after discharge due to sepsis and neurological shock. Major bleeding manifestations more in HR as compared to IR group. Conclusions: Tenectaplase is a potent thrombolytic agent which can be used as the drug of choice for acute PE of usual causes without many complications. Prompt diagnosis and treatment of PE with potent thrombolytics can be life-saving.